Prispevek k poznavanju razširjenosti metuljev (Macrolepidoptera) subpanonskega dela slovenske Štajerske - Lesar, Tone (Acta entomologica slovenica (Ljubljana), 2006)
40 butterfly and moth species newly and unexpectedly found in the subpannonianpart of Slovene Štajerska according to the Red list (Carnelutti 1992a, b) are presented. First data for 16 species are published, in other species the new data are mentioned beside already published ones. 7 protected species are listed that give the region its value for nature-conservation.
Keywords: entomologija; metulji; Slovenia; Slovenija; Styria; Štajerska